2009
DOI: 10.1029/2008gl036259
|View full text |Cite
|
Sign up to set email alerts
|

Forcing of resonant modes on a fringing reef during tropical storm Man‐Yi

Abstract: [1] Open basin resonant modes have been observed at tidal frequencies on coastal shelves, but their excitation on coral reef platforms has only been suggested. The topography of and water depth over most fringing reefs correspond to resonant periods that are the order of tens of minutes and fall outside of the energetic part of the wave spectrum. During tropical storm Man-Yi, low frequency near resonant oscillations dominated the variance of the sea surface elevation at the shoreline of Ipan reef, Guam. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 26 publications
9
102
1
2
Order By: Relevance
“…The mechanism is strong enough that, on shallow, wide reefs, the IG wave energy may dissipate significantly before reaching the shoreline (Pomeroy et al, 2012). In the case of the Majuro Atoll study site during the inundation event, we do see evidence for shoreline reflection and subsequent excitation of a one-quarter wavelength, quasistanding mode, similar to that reported during an inundation event at a fringing reef at Ipan, Guam (Péquignet, 2009). That analysis is supported by the findings that the peak frequency of the IG energy (f p~0 .007 Hz) on the reef flat is consistent with that of a one-quarter wavelength mode (FBM2012 Figure 10) and that the amplitude of the IG energy on the reef flat increases shoreward, consistent with the spatial structure of a onequarter wavelength mode and inconsistent with frictional dissipation of a shoreward propagating IG wave.…”
Section: (2) Nonlinear Energy Transfer Between Ss and Ig Wavessupporting
confidence: 65%
“…The mechanism is strong enough that, on shallow, wide reefs, the IG wave energy may dissipate significantly before reaching the shoreline (Pomeroy et al, 2012). In the case of the Majuro Atoll study site during the inundation event, we do see evidence for shoreline reflection and subsequent excitation of a one-quarter wavelength, quasistanding mode, similar to that reported during an inundation event at a fringing reef at Ipan, Guam (Péquignet, 2009). That analysis is supported by the findings that the peak frequency of the IG energy (f p~0 .007 Hz) on the reef flat is consistent with that of a one-quarter wavelength mode (FBM2012 Figure 10) and that the amplitude of the IG energy on the reef flat increases shoreward, consistent with the spatial structure of a onequarter wavelength mode and inconsistent with frictional dissipation of a shoreward propagating IG wave.…”
Section: (2) Nonlinear Energy Transfer Between Ss and Ig Wavessupporting
confidence: 65%
“…However, few reef studies (e.g. Lugo-Fernández et al, 1998;Péquignet et al, 2009) have recorded resonant oscillations in the field, with the most convincing study being that on Guam during tropical storm Man-Yi (Péquignet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kirby et al, 2006). It has been postulated that for coastal environments characterized by fringing reefs, resonant low frequency wave oscillations may be responsible for coastal damage observed during typhoons (Nakaza and Hino, 1991) or tropical storms (Péquignet et al, 2009). However, few reef studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that this physical mechanism can increase the coastal flooding hazard (e.g. Péquignet et al, 2009), and hence its contribution to the wave-induced water level variability needs to be considered.…”
Section: Introductionmentioning
confidence: 99%